1979
DOI: 10.1073/pnas.76.12.6500
|View full text |Cite
|
Sign up to set email alerts
|

Human heterozygosity: a new estimate.

Abstract: Several hundred polypeptides from four human diploid fibroblast cell lines were compared by high-resolution two-dimensional polyacrylamide gel electrophoresis and double-label autoradiography under conditions where allelic products that differ by a single charged amino acid would be distinguished. The average heterozygosity represented by this set of gene products appears to be less than 1% for changes involving charged amino acids.The nature and extent of genetic diversity among humans is a matter of great th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
2

Year Published

1982
1982
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 22 publications
3
28
2
Order By: Relevance
“…The rule that emerges is that loci that are highly variable under one condition of detection McConkey et al, 1979;Racine and Langley, 1980). A similar result was obtained when several groups of water-soluble proteins of non-enzymatic nature were analyzed electrophoretically .…”
Section: Genetic Monomorphism Of Species As a Real Natural Phenomenonsupporting
confidence: 53%
“…The rule that emerges is that loci that are highly variable under one condition of detection McConkey et al, 1979;Racine and Langley, 1980). A similar result was obtained when several groups of water-soluble proteins of non-enzymatic nature were analyzed electrophoretically .…”
Section: Genetic Monomorphism Of Species As a Real Natural Phenomenonsupporting
confidence: 53%
“…In addition, the frequency of transcript data from whole brain could be misleading because the extreme cellular heterogeneity in the CNS would tend to reduce the copy number for each cell that is actually synthesizing the protein. Finally, it is unlikely that polymorphic differences between individual rats could significantly alter the above data, for the majority of the cell lines were from the BDIX inbred strain, and the average heterozygosity between human fibroblasts is less than 1% as defined by 2D gel analysis (McConkey et al, 1979;Walton et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Virtually no information exists concerning levels of genetic variation of membrane bound proteins. Some data has been collected using two dimensional electrophoresis (Comings 1979;McConkey, Taylor and Phan 1979;Smith, Racine and Langley 1980), although the interpretation of the resolving power of 2-D electrophoresis remains somewhat questionable (Edwards and Hopkinson 1980;Warner, Neel and Meisler 1982;McLellan, Ames and Nikaido 1983). We can say nothing concerning possible effects of GMPTM on levels of variation estimated using these techniques.…”
Section: Other Classes Of Locimentioning
confidence: 99%
“…Some of these methods may increase the estimated average heterozygosity in a population, compared to the values obtained by more traditional screening methods, because they separate previously undifferentiated alleles (Ayala 1982), while others may have an unknown effect because they are increasing the number and type of loci which are being sampled, but with an undetermined sensitivity to allelic differences (McConkey, Taylor and Phan 1979;McLellan, Ames and Nikaido 1983). Nei and Roychoudhury (1982) reanalyzed the data on genetic variation in major racial groups and reported that average heterozygosity levels for protein loci were increased to the range 12-16% when they included loci for which new screening methods (excluding two-dimensional electrophoresis) had been used during the collection of gene frequency data.…”
Section: Introductionmentioning
confidence: 99%